Coplanar asymmetric angles and symmetric energy sharing triple differential cross sections for 200 eV electron-impact ionization of Ar (3p). (August 2015) - Ozer, Zehra N; Amami, Sadek; Varol, Onur; Yavuz, Murat; Dogan, Mevlut; Madison, Don
Synopsis: We have measured triple differential cross sections (TDCSs) for electron-impact ionization of the 3p shell of Ar at 200 eV incident electron energy. The experiments have been performed in coplanar asymmetric energy sharing geometry. The experimental results are compared with the theoretical models of three body distorted wave (3DW) and distorted wave Born approximation (DWBA).